Climate Change Impacts on Agricultural Weeds in Western Australia - Michael, Pippa; Yeoh, P.; Ota, N.; Scott, J. (Rural Industries Research and Development Corporation, 2011)
Foreword: Weeds cost Australian agriculture over $4 billion annually through factors such as yield loss and management costs. Although not quantified, the impact of weeds on natural ecosystems has also been recognised as a serious threat to biodiversity. Consequently there is a significant need to understand the factors that influence the distribution, spread and abundance of invasive weed species in agriculture, under both current and future environmental and management conditions.